Iterative reconstruction in single source dual-energy CT pulmonary angiography: Is it sufficient to achieve a radiation dose as low as state-of-the-art single-energy CTPA?. Issue 11 (November 2015) - Ohana, M.; Labani, A.; Jeung, M.Y.; Ghannudi, S.El; Gaertner, S.; Roy, C.
Graphical abstract: Highlights: Iterative reconstruction can be applied to single source dual-energy examinations. Single source DE-CTPA are thus obtained without increasing the radiation dose. A wider use of the dual-energy technique could therefore be advocated. mA adjustment in correlation with the BMI should offer the best compromise. Abstract: Objective: Dual-energy (DE) brings numerous significant improvements in pulmonary CT angiography (CTPA), but is associated with a 15–50% increase in radiation dose that prevents its widespread use. We hypothesize that thanks to iterative reconstruction (IR), single source DE-CTPA acquired at the same radiation dose that a single-energy examination will maintain an equivalent quantitative and qualitative image quality, allowing a more extensive use of the DE technique in the clinical routine. Material and methods: Fifty patients (58% men, mean age 64.8yo ± 16.2, mean BMI 25.6 ± 4.5) were prospectively included and underwent single source DE-CTPA with acquisition parameters (275 mA fixed tube current, 50% IR) tweaked to target a radiation dose similar to a 100 kV single-energy CTPA (SE-CTPA), i.e., a DLP of 260 mGy cm. Thirty patients (47% men, 64.4yo ± 18.6, BMI 26.2 ± 4.6) from a previous prospective study on DE-CTPA (375 mA fixed tube current, reconstruction with filtered-back projection) were used as the reference group. Thirty-five consecutive patients (57% men, 65.8yo ± 15.5, BMI 25.7 ± 4.4) who underwent SE-CTPA on the same scanner (automated tube current modulation, 50% IR) served as a comparison. Subjective image quality was scored by two radiologists using a 5-level scale and compared with a Kruskal–Wallis nonparametric test. Density measurements on the 65 keV monochromatic reconstructions were used to calculate signal-to-noise (SNR) and contrast-to-noise (CNR) ratios that were compared using a Student's t test. Correlations between image quality, SNR, CNR and BMI were sought using a Pearson's test. p  < 0.05 was considered significant. Results: All examinations were of diagnostic quality (score ≥ 3). In comparison with the reference DE-CTPA and the SE-CTPA protocols, the DE-IR group exhibited a non-inferior image quality ( p  = 0.95 and p  = 0.21, respectively) and a significantly lower mean image noise ( p  < 0.01 and p  = 0.01) thus slightly improving the SNR ( p  = 0.09 and p  = 0.47) and the CNR ( p  = 0.12 and p  = 0.51). There was a strong negative relationship between BMI and SNR/CNR ( ρ  = −0.59 and −0.55 respectively), but only a moderate negative relationship between BMI and image quality ( ρ  = −0.27). Conclusion: With iterative reconstruction, objective and subjective image quality of single source DE-CTPA are preserved even though the radiation dose is lowered to that of a single-energy examination, overcoming a major limitation of the DE technique and allowing a widespread use in the clinical routine.